Kalantaevska G. P., Savchenko I. V. Typesand charactersof childrenin stroiesof E. Gutsalo - Kalantaevska G. P.; Savchenko I. V. (Philological Treatises, 2020)
The article deals with E. Gutsalo’s representation of children types and characters against the backdrop of war and postwar period in the context of school life, family relationships, communication with fellows. It analyses the spiritual world and the psychology ofchildren and adolescents, their interests, valuesand priorities.